The safety of packaged food: focus on environmental management and the food regulation 1985 - Norul Hajar Nordin,; Muhammad Rizal Razman,; Sharifah Zarina Syed Zakaria, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
Issue of food safety is an important issue that related to public safety to prevent the toxicity threats of the food. If consumers eat contaminated food with dirt and germs, they will involve with Food Water Borne Disease otherwise known as (FWBD). Food packaging is look as an approach to overcome and reduce the toxicity of food in dealing with environmental management. Sometimes the packaging can considered as a source of risk to the food and rarely considered as a technology that can used to improve the safety of the food. Therefore, the Food Regulation 1985 is one mechanism of environmental management through legal approach in controlling the safety of packaged food. This article tends to analyse and to explain the implementation of the Food Regulation 1985 in controlling the safety of packaged food. Meanwhile, the methods of this study are based on qualitative set up, which is based on primary document, the Food Regulation 1985 and the result, there are 2 main themes, general and specific, while their 7 sub themes are included harmful packages, safety packages, reuse packages, polyvinyl chloride (PVC), alcoholic bottle, toys, money and others and iron powder. The effectiveness and the implementation of the Food Regulation 1985 in controlling the safety of packaged food did not depend and focused only to the Food Regulation 1985. But due to overcome the food poisoning and other disease that related to Food Water Borne Disease (FWBD), it must involve the usage and acceptance a few legislation which related to the safety of packaged food with enforcement from local government and other mechanisms of environmental management.